Development of interactive software (shear force and bending moment) - Tan, Derrick Kai Keong (Nanyang Technological University, 2020)
An interactive software application developed to provide all shear forces and bending moment acting on the beam. Software are developed using the Direct Stiffness Matrix Method to solve the beam’s problem and able to solve any problems regardless is it a statically determinate problem or a statically indeterminate problem. A Shear Force Diagram and Bending Moment Diagram shall be provided after each problem solved for analysis purposes. Problems with or without Modulus of Elasticity and Moment of Inertia can be solved by the software with the correct shear force and bending moment at each node. However, if actual Modulus of Elasticity and Moment of Inertia not used stiffness matrix and deflection value should not be treated as the actual value. The software is developed using JavaScript as the backbone for interactive software. JavaScript is currently the most popular programming language as it is straightforward since it does not require any initial setup to start programming and the program are written in plain text format. JavaScript is also the fastest compared to other programming languages as it is built on a V8 Chrome engine which is one of the fastest in the world. It can also be used as front-end and back-end language making it the popular language. Canvas are used to provide interactive in the software and used to draw all diagrams in the program. The program will be useful for all engineering students and can be used for understanding the Mechanics of Materials concepts.